ACTIVITY BASED COSTING METHOD IN DETERMINING UNIT COST OF LITHOTRIPSY FOR TREATMENT OF URINARY BLADDER CALCULUS AT VITA INSANI HOSPITAL PEMATANGSIANTAR - Nasution, Muhammad Andriady Saidi; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (Indonesian Journal of Urology, 2022)
Objective: To determine the unit cost of lithotripsy for treatment of urinary bladder calculus at Vita Insani Hospital Pematangsiantar. Material & Methods: This study is a descriptive quantitative study, in which the data was obtained from the finance division of Vita Insani Hospital. The research object is the unit cost of accommodation that occurs in patients with urinary bladder calculus with lithotripsy cases from January 2020 to December 2020. Results: The unit cost of lithotripsy for urinary bladder calculus services at Vita Insani Hospital Pematangsiantar which is calculated using the activity-based costing (ABC) method is Rp 4.167.009. There is a difference in cost among the ABC method, hospital calculations, and INA CBG’s rates with the following details: the amount calculated for the hospital is Rp 4.996.718, while the calculation using ABC method is Rp 4.167.009; the difference in costs is Rp 829.709. INA CBG’s rates Rp 6.137.500, and compared to calculation of hospital, the difference cost is Rp 1.140.782. Compared to the INA CBG’s rates, to the unit cost of the ABC method, there is a difference, amounting Rp 1.970.491. Conclusion: The results of unit cost lithotripsy for treatment of urinary bladder calculus through the ABC method are lower compared to hospital calculation and INA CBG’s rates.